2018 IEEE International Conference on Big Data (Big Data) 2018
DOI: 10.1109/bigdata.2018.8621884
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effects of News Sentiments on the Stock Market

Abstract: Stock market forecasting is very important in the planning of business activities. Stock price prediction has attracted many researchers in multiple disciplines including computer science, statistics, economics, finance, and operations research. Recent studies have shown that the vast amount of online information in the public domain such as Wikipedia usage pattern, news stories from the mainstream media, and social media discussions can have an observable effect on investors' opinions towards financial market… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…Dev Shah et al [5] had studied the news and on the basis of that news they had do the sentiment analysis. In this paper they had find out the polarity for pharma sector.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Dev Shah et al [5] had studied the news and on the basis of that news they had do the sentiment analysis. In this paper they had find out the polarity for pharma sector.…”
Section: Literature Surveymentioning
confidence: 99%
“…Business: In advancing field firms use it to build up their strategies, to know clients' sentiments towards product or entire, people answer their battles or item dispatches and why customers don't get some product [1] [5].…”
Section: Sentiment Intensity Analyzermentioning
confidence: 99%
“…News is relatively objective due to its reliance on facts, but social data can be based on facts or rumours created by other investors; thus social data is quite subjective (Jeong et al, 2018). In stock price prediction, in addition to historical prices, research have proven that financial news and social media can improve the accuracy of stock price prediction (Zhang et al, 2018;Shah et al, 2018). SA becomes an important process used to extract facts or moods from media and many SA techniques are used for the stock price prediction in existing research, summarised below.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…The results exhibited significant performance of the stock market prediction model as well as preserved results interpretability. Shah et al analyzed the effects of news sentiments on the stock market [19]. They developed a dictionary-based sentiment analysis model and reported that news articles are powerful indicators for predicting short-term stock price movement.…”
Section: A Stock Prediction Advocates Related Workmentioning
confidence: 99%